False-negative Results with the Bethesda System of Reporting Thyroid Cytopathology: Predictors of Malignancy in Thyroid Nodules Classified as Benign by Cytopathologic Evaluation. Issue 8 (August 2014) - Richmond, Bryan K.; Judhan, Rudy; Chong, Benny; Ubert, Adam; Aburahma, Zachary; Mangano, William; Thompson, Stephanie
The benign category of the Bethesda System for reporting thyroid cytopathology (BSRTC) predicts an incidence of malignancy from zero to three per cent. However, recent series report higher rates of malignancy ranging from eight to 14 per cent. Surgery is often performed for reasons other than their fine needle aspiration biopsy (FNAB) such as symptoms, nodule enlargement, or worrisome imaging. We hypothesized that an analysis of patients who underwent thyroidectomy despite a benign FNAB would identify predictors of malignancy, an area not currently addressed by American Thyroid Association guidelines. We performed a retrospective analysis of patients with benign FNAB results who underwent thyroidectomy from October 2007 to October 2012. Data collected included symptoms, imaging findings, FNAB results, and operative and histopathology results, all of which were obtained by chart review. Findings were compared between patients with and without a diagnosis of malignancy. Statistical significance was set as P < 0.05. Of 3839 FNABs, 2838 were benign. Of these, 180 underwent surgery for indications other than the FNAB category. Twenty-four (13.4%) malignancies were identified: 12 (6.7%) incidental microcarcinomas and 12 (6.7%) significant cancers (papillary greater than 1.0 cm, any nonpapillary histology). No patient's symptoms or signs reached significance as a predictor of malignancy. Suspicious ultrasound appearance was significantly associated with an underlying carcinoma ( P = 0.004). The false-negative result with benign FNAB is higher in surgical series than suggested by the BSRTC. Patients with tolerable symptoms may be observed in the face of a benign FNAB. Additionally, despite a benign FNAB, recommendations for closer follow-up or surgical intervention are warranted if the ultrasound appearance is suspicious.